The Politics of Legality and UN Resolution 2334 - Yogendran, Sangeetha (2017)
UN Resolution 2334 condemning Israeli settlements was passed by the Security Council only because the US did not exercise its usual veto. As expected, the resolution was strongly opposed by Israel, which threatened to cut its funding to the United Nations. As we face an uncertain global order, it is crucial that countries work within the international system.